Tacrine derivatives as dual topoisomerase I and II catalytic inhibitors - Janočková, Jana; Plšíková, Jana; Koval', Ján; Jendželovský, Rastislav; Mikeš, Jaromír; Kašpárková, Jana; Brabec, Viktor; Hamuľaková, Slávka; Fedoročko, Peter; Kožurková, Mária (Bioorganic chemistry, 2015)
This study examines the binding properties of a series of newly synthetized tacrine derivatives 1-4 and their anticancer effects. Spectroscopic techniques (UV-Vis, fluorescence spectroscopy, thermal denaturation, and linear spectropolarimetry) and viscometry were used to study DNA binding properties and to determine the types of DNA interaction with the studied derivatives. The binding constants for the complexes with DNA were obtained using UV-Vis spectroscopic titrations (K = 1.6 × 10(4)-4.0 × 10(5) M(-1)) and electrophoretic methods were used to determine the effect of the derivatives on topoisomerase I and II activity. Monotacrine derivative 1 showed evidence of topoisomerase Irelaxation activity at a concentration of 30 × 10(-6) M, while bistacrine derivatives 2-4 produced a complete inhibition of topoisomerase Iat a concentration of 5 × 10(-6) M. The biological activities of the derivatives were studied using MTT-assay and flow cytometric methods (detection of mitochondrial membrane potential and measurement of cell viability) following incubation of 24 and 48 h with human leukemic cancer cell line HL60. The ability of the derivatives to impair cell proliferation was also tested through the analysis of cell cycle distribution.
Keywords: proliferace buněk; apoptóza; HL-60 buňky; Topoisomerase II Inhibitors; Intercalating Agents; DNA-topoisomerasy; Topoisomerase I Inhibitors; Apoptosis; DNA; lidé; Antineoplastic Agents; protinádorové látky; inhibitory topoisomerasy II; HL-60 Cells; Topoisomerase I and II; interkalátory; DNA Topoisomerases; takrin; Tacrine; leukemie; Spectroscopic techniques; Cell Proliferation; Leukemia; inhibitory topoisomerasy I; Tacrine derivatives; Humans